Ravine Development in Tundra (Osobennosti Ovrazhnoi Erozii v Tundre) - Kosov,B. S.; Konstantinova,G. S. (1972)
The report describes in detail the effect of permafrost on ravine erosion and development. Draft trans. of mono. Eroziya Pochv i Ruslovye Protsessy (Soil Erosion and Fluvial Processes), Moscow, 1970 v1 p152-161.